Perancangan Web Kuliner Dengan Menggunakan Pendekatan Pattern Based Requirement - Afifurrijal Afifurrijal; Adam Hendra Brata; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Culinary is one part of daily lifestyle that cannot be separate because every human being needs food for daily consumption (KBBI, 2003). ). In 2019 the culinary industry become a superior subsector of the creative economy by contributing a contribution of 264 billion to Gross Domestic Product (Kominfo, 2019). From these data it can be said that the income from the culinary business is profitable. One way to get profit is to promote business via the internet through a website. In every case of software development on a website, of course it produces certain needs with frequent frequency, creating a pattern of needs that can be used on a pattern of software requirements. One method that can be used to simplify the software development process is pattern based requirements that will produce patterns of software requirements.After got the pattern requirement,then obtained fungtional requirement and designing with platform code igniter. Designing using approach object oriented. Testing is done using basic testing and quality testing. From the tests conducted, it was found that all artifacts had been made based on use cases and also the results of the design had a low coupling and high understandability value because the value of the CBO (Coupling Between Object Classes) was 1 and the RFC (Response for a Class) value was 3 The results of the design also have a low cohesion value due to the value of LCOM1 (Lack of Cohesion Method 1) and the value of adaptability is high because the CBO value is between 1-3, the RFC value is between 1-69 and meets the LCOM2 value (Lack of Cohesion Method 2).